Household Electrification and Indoor Air Pollution - Barron, Manuel; Torero, Maximo (Elsevier, 2018)
This paper provides the first experimental evidence that household electrification leads to substantial reductions in indoor air pollution. Two years after electricity rollout, we measured overnight fine particulate matter (PM2.5) concentration, which was on average 66% lower among households that were randomly encouraged to connect to the electrical grid compared to those that were not. As a result, prevalence of acute respiratory infections among children under six was 8-14 percentage points lower in the former group. We find suggestive evidence that these changes are at least partly driven by reductions in kerosene use.